Simultaneous Single Dexamethasone Implant and Ranibizumab Injection in a Case with Active Serpiginous Choroiditis and Choroidal Neovascular Membrane - Saatci, Ali Osman (Case Rep Ophthalmol, 2015)
Intravitreal anti-vascular endothelial growth factor (VEGF) agents seem to be effective in choroidal neovascular membranes (CNV) in association with various entities of posterior uveitis. We herein report a 46-year-old woman who was treated with a simultaneous single intravitreal dexamethasone implant and ranibizumab administration for the treatment of unilateral extrafoveal CNV associated with an active serpiginous choroiditis. Simultaneously with the intravitreal therapy, oral mycophenolic acid (2 × 720 mg) was started, and oral cyclosporine (3 × 100 mg) was then added 2 months later. On the other hand, the fellow eye had been treated for subfoveal CNV but with an inactive disease 4 years previously and ended up with a final visual acuity of counting fingers despite treatment with a single session of photodynamic therapy and 3 subsequent intravitreal ranibizumab injections. Simultaneous administration of anti-VEGF agents and a dexamethasone implant can be a viable approach in eyes with CNV and active serpiginous choroiditis.